Integration of ultra-high field MRI and histology for connectome based research of brain disorders - Yang, Shan; Yang, Zhengyi; Fischer, Karin; Zhong, Kai; Stadler, Jörg; Godenschweger, Frank; Steiner, Johann; Heinze, Hans-Jochen; Bernstein, Hans-Gert; Bogerts, Bernhard; Mawrin, Christian; Reutens, David; et al. (Frontiers in Neuroanatomy, 2013)
Ultra-high field magnetic resonance imaging (MRI) became increasingly relevant for in vivo neuroscientific research because of improved spatial resolutions. However, this is still the unchallenged domain of histological studies, which long played an important role in the investigation of neuropsychiatric disorders. While the field of biological psychiatry strongly advanced on macroscopic levels, current developments are rediscovering the richness of immunohistological information when attempting a multi-level systematic approach to brain function and dysfunction. For most studies, histology sections lost information on three-dimensional reconstructions. Translating histological sections to 3D-volumes would thus not only allow for multi-stain and multi-subject alignment in post mortem data, but also provide a crucial step in big data initiatives involving the network analyses currently performed with in vivo MRI. We therefore investigated potential pitfalls during integration of MR and histological information where no additional blockface information is available. We demonstrated that strengths and requirements from both methods seem to be ideally merged at a spatial resolution of 200 μm. However, the success of this approach is heavily dependent on choices of hardware, sequence and reconstruction. We provide a fully automated pipeline that optimizes histological 3D reconstructions, providing a potentially powerful solution not only for primary human post mortem research institutions in neuropsychiatric research, but also to help alleviate the massive workloads in neuroanatomical atlas initiatives. We further demonstrate (for the first time) the feasibility and quality of ultra-high spatial resolution (150 µm isotopic) imaging of the entire human brain MRI at 7T, offering new opportunities for analyses on MR-derived information.